Analysis Of The Application Of Renewable Energy At The Muara Angke Passenger Port As A Means Of Supporting Thousand Island Tourism - Arif Fadillah; Fuad Maulana (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Kepulauan seribu are also a frequently visited destination for domestic and foreign tourists and are among the priority destinations in Indonesia. The development of the passenger port in Muara Angke is an important step in supporting the tourism sector in Kepulauan Seribu. However, this development must also consider environmental impacts, including carbon emissions and the use of natural resources. Indonesia has taken steps towards developing renewable energy and policies that support it by implementing renewable energy at the Muara Angke Passenger Port will be in line with government initiatives to achieve energy targets national renewable. The method used is primary data, secondary data, by calculating the need for solar panels and wind turbines and collecting supporting data sourced from related websites. The results are 324 solar panels placed on the roof of the main building of the port where the wind turbine is placed on the west side. with a total of 6 units, on the east side of the port there are 6 units and on the south side of the port there are 4 wind turbine units